2014
DOI: 10.1590/s0100-06832014000100018
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxidation on the surface of adventitious roots and its relation to aerenchyma formation in rice genotypes

Abstract: Establishment of the water layer in an irrigated rice crop leads to consumption of free oxygen in the soil which enters in a chemical reduction process mediated by anaerobic microorganisms, changing the crop environment. To maintain optimal growth in an environment without O2, rice plants develop pore spaces (aerenchyma) that allow O2 transport from air to the roots. Carrying capacity is determined by the rice genome and it may vary among cultivars. Plants that have higher capacity for formation of aerenchyma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A wide variety of plants were proven to form IP, comprising underwater plants, emergent plants, terrestrial plants in aquatic environments, and so on. Representatives of Previous studies have shown that IP is more likely to occur in acidic pH environments [61,62]. After a series of redox reactions, it ultimately precipitates on the root surface in the form of Fe 2 O 3 or Fe(OH) 3 [20].…”
Section: Formation Of Ipmentioning
confidence: 89%
See 2 more Smart Citations
“…A wide variety of plants were proven to form IP, comprising underwater plants, emergent plants, terrestrial plants in aquatic environments, and so on. Representatives of Previous studies have shown that IP is more likely to occur in acidic pH environments [61,62]. After a series of redox reactions, it ultimately precipitates on the root surface in the form of Fe 2 O 3 or Fe(OH) 3 [20].…”
Section: Formation Of Ipmentioning
confidence: 89%
“…In the middle and late stages, through the equation of 4Fe(II) + 10H2O + O2 → 4Fe(OH)3 + 8H + [58][59][60], Fe(II) is transformed into iron oxide, which precipitates on the surface of the roots, thus forming IP and protecting plant roots from HMs via adsorption. Previous studies have shown that IP is more likely to occur in acidic pH environments [61,62]. After a series of redox reactions, it ultimately precipitates on the root surface in the form of Fe2O3 or Fe(OH)3 [20].…”
Section: Formation Of Ipmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerenchyma was formed up to 20-50% of the total volume of rice root in a flooded condition. The aerenchyma formation was started from 2-4 weeks after planting, and the highest oxidation ability occurred in the maximum tiller formation stage [39]. The Fe concentration did not affect the total of the tiller ( Table 3).…”
Section: Growth Componentsmentioning
confidence: 93%